2002
DOI: 10.1007/s10024-001-0260-6
|View full text |Cite
|
Sign up to set email alerts
|

Value of Autopsy in Nonimmune Hydrops Fetalis: Series of 51 Stillborn Fetuses

Abstract: Nonimmune hydrops fetalis (NIHF) is used to describe fetuses and newborns with generalized edema and cavity effusions. It is helpful to alert physicians about the presence of anemia, heart failure, and/or hypoproteinemia, but this diagnosis is frequently overlooked. We reviewed the autopsy files from 1990 to 2000, selected all cases with NIHF including clinical information (with maternal laboratory tests and ultrasound), and classified patients by etiology. Among 840 stillborn autopsies during the 11-year peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 8 publications
4
46
1
Order By: Relevance
“…Fetal ascites is generally a symptom of underlying pathology [1,[3][4][5] . This report widens the knowledge regarding the pathogenesis of the fetal ascites, showing a connection between this clinical finding and the vascular wall necrosis in utero of one umbilical artery [3,4] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fetal ascites is generally a symptom of underlying pathology [1,[3][4][5] . This report widens the knowledge regarding the pathogenesis of the fetal ascites, showing a connection between this clinical finding and the vascular wall necrosis in utero of one umbilical artery [3,4] .…”
Section: Discussionmentioning
confidence: 99%
“…Serial sections of the cord showed an increase in the necrosis and collapse distally from the placenta. Large groups of chorionic villi, which were mainly of the immature intermediate type, showed stromal edema, disruption of the reticular spaces, and Hofbauer cells with enlarged multivacuolated cytoplasm, features not consistent with congenital infections or congenital metabolic disorders [5,6] ( fig. 2 ).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors have suggested that revision of current follow-up criteria may be necessary if extended viraemia is a more common occurrence than heretofore thought. Rodriguez et al (2002Rodriguez et al ( , 2005 have undertaken the analysis of NIFH in both stillborn and livebirth autopsy scenarios. Following the evaluation of 840 stillborn autopsies (Rodriguez et al, 2002), 51 cases of NIFH were observed which represented 6.07% of all stillbirths.…”
Section: Successfulmentioning
confidence: 99%
“…Rodriguez et al (2002Rodriguez et al ( , 2005 have undertaken the analysis of NIFH in both stillborn and livebirth autopsy scenarios. Following the evaluation of 840 stillborn autopsies (Rodriguez et al, 2002), 51 cases of NIFH were observed which represented 6.07% of all stillbirths. Congenital infection, caused either by bacterial or viral infection was identified in 17 of the 51 cases of NIFH of which B19 was uniquely identified in four cases (7.8%).…”
Section: Successfulmentioning
confidence: 99%